EFFECT OF COVID-19 CORONAVIRUS ON MAJOR NORTH EFFECT OF COVID-19 CORONAVIRUS ON MAJOR NORTH AMER-ICAN SPORTS LEAGUESAMER-ICAN SPORTS LEAGUES - Váczi, Péter; Müller, Anetta; Bácsné Bába, Éva (Acta Carolus Robertus, 2021)
The coronavirus epidemic has had a big impact on all areas of our lives, even on elite sports. In the situation caused by the epidemic, sports clubs, sports associations, but even entire sports were in an extremely difficult situation. Sport has become a business in the last 20-30 years, and top athletes have become products. The highest levels of business-based sports businesses are found in the United States and the European football market. In this dissertation, I will examine the impact of the coronavirus on the four major sports leagues operating in the North American franchise system. I will present not only the effects caused by the virus, but also the possible solutions, and then I will try to draw conclusions and suggestions from the revealed information.